Some blood parameters in dairy cows with fatty liver syndrome - Some blood parameters in dairy cows with fatty liver syndrome (Eurasian Journal of Veterinary Sciences)
In this study, a total of 23 dairy cows were used. Blood and liver biopsy samples were obtained from eoxh animal before and after calving. Plasma total lipid, the percentages of different leucocyte types and fatty infiltration of the liver were estimated in animals. Plasma total lipid values increased significantly (P< 0.05), the percentage of the lymphocytes decreased in dairy cows associated with fatty liver syndrome after calving.